2018
DOI: 10.1186/s13065-018-0406-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of heterocyclic pyrimidine scaffolds

Abstract: Heterocyclic compounds offer a high degree of structural diversity and have proven to be broadly and economically useful as therapeutic agents. Comprehensive research on diverse therapeutic potentials of heterocycles compounds has confirmed their immense significance in the pathophysiology of diseases. Heterocyclic pyrimidine nucleus, which is an essential base component of the genetic material of deoxyribonucleic acid, demonstrated various biological activities. The present review article aims to review the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 62 publications
0
81
0
Order By: Relevance
“…The reactions took place both under conventional TH and MW irradiation, the use of MW having the advantages of obtaining slightly higher yields of the products and a substantial decrease of the reaction time from 8 h to 30 min. Using click chemistry (from the corresponding coumarin azide (48,50) and triple bond compounds), Kraljević et al [35] obtained 4-substituted 1,2,3-triazole coumarins 49a-p and 51a-f. The reaction took place under MW irradiation in good to very good yields (50 to 95%) and one hour reaction time.…”
Section: Five Membered Ring Azaheterocycles With More Than Two Heteromentioning
confidence: 99%
See 2 more Smart Citations
“…The reactions took place both under conventional TH and MW irradiation, the use of MW having the advantages of obtaining slightly higher yields of the products and a substantial decrease of the reaction time from 8 h to 30 min. Using click chemistry (from the corresponding coumarin azide (48,50) and triple bond compounds), Kraljević et al [35] obtained 4-substituted 1,2,3-triazole coumarins 49a-p and 51a-f. The reaction took place under MW irradiation in good to very good yields (50 to 95%) and one hour reaction time.…”
Section: Five Membered Ring Azaheterocycles With More Than Two Heteromentioning
confidence: 99%
“…Using click chemistry (from the corresponding coumarin azide (48,50) and triple bond compounds), Kraljević et al [35] obtained 4-substituted 1,2,3-triazole coumarins 49a-p and 51a-f. The reaction took place under MW irradiation in good to very good yields (50 to 95%) and one hour reaction time.…”
Section: Five Membered Ring Azaheterocycles With More Than Two Heteromentioning
confidence: 99%
See 1 more Smart Citation
“…A small library of LSD1 inhibitors was acquired through commercial and collaborative sources or from information derived from a recent large-scale RNAi investigation of S. mansoni gene function [38] (Fig 1 and S1 Table). This collection included the only FDA-approved LSD1 inhibitor, trans-2-Phenylcyclopropylamine, (2-PCPA or better known as tranylcypromine (1) [35]), several small molecules undergoing clinical testing (including GSK-LSD1 (2) [39], ORY-1001 (3) [40] and GSK2879552 (8) [41]), pharmacologically active compounds synthesised around a substituted lysine scaffold (compounds 9 and 10 [42,43], the latter currently in clinical trial for the treatment of myelofibrosis [44]) and a selection of derivatised chemicals (compounds 11-38) [27,45]. This collection also included two dual LSD1/HDAC inhibitors (compounds 6 and 7) [26] designed as hybrid compounds resulting from the combination of a standard HDAC zinc binding group (benzamide group of Entinostat (MS-275) [46]) to either a phenelzine derivative (4, also known as Bizine [47]) or a cyclopropylamine analog of Bizine (5, [48]), respectively.…”
Section: Hslsd1 Inhibitors Differentially Affect Schistosomula Phenotmentioning
confidence: 99%
“…Substituted pyrimidine derivatives (non-nucleosides) are found to be associated with various biological activities, including activity against different DNA and RNA viruses. 28 Previously, we showed that some pyrimidine derivatives have potent in vitro antiviral activity against polyovirus-3. 29 The present study focuses on the anti-BKV activity of pyrimidine derivatives which were synthesized at V.P.…”
Section: Introductionmentioning
confidence: 99%